Evolutionary Relationship of Common Mangoes: Insight from ITS - HAYATI, IBNA; , FITMAWATI; SOFIYANTI, NERY (Jurnal Riau Biologia, 2016)
Mango (Mangifera) is one the most important fruit from Asia. The center of origin and diversity of this genus is in Southeast Asia. This region has great economic development in recent years. Due to the deforestation and habitat change, the occurance of Mangifera species in their natural habitat is threathened. This research aimed to analyze evolutionary relationship among common mangoes from Central Sumatra. This research was conducted from November 2015 until April 2016. DNA was isolated using CTAB method. The isolated DNA were then sequenced in First Base Laboratories, Malaysia. Phylogram was generated using Neighbor Joining Method, while T92+G evolution model was used for Distance Analysis. NJ analysis revealed monophyletic group of common mangoes. M. laurina was considered as the most primitive species in common mangoes clade due to the longest branch length. Relationship among M. kemanga and M. laurina, M. indica and M. zeylanica was a new finding. It would be highlighted to determine newer classification, cultivation and conservation strategies of mango.Â